Ways To Implement Innovations in The Development of The Hotel Industry in Uzbekistan - Tokhirov Javlon Rakhimovich; Hamidov Saidjon Kamilovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This article is devoted to ways to implement innovations in the development of the hotel industry in Uzbekistan. In particular, the main motives for innovation and sales in the hotel services are increasing market position, increasing the competitiveness of new products, capturing new markets, increasing cash flow, reducing resource consumption of products